(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The article presents research data from 60 patients with vascular dementia. All subjects were divided into 2 groups: 1st group - 30 patients who received choline alfoscerate on the background of basic therapy; and group 2 - 30 patients who received only basic therapy. The effectiveness of therapy was evaluated twice: before treatment and on day 40 of treatment. The status was assessed using the VAS scale (visual-analogue scale for pain), according to the questionnaire for identifying vegetative disorders and determining the vegetative dystonia syndrome (VDS), according to the severity of vegetative reactivity according to the Danyini-Ashner test, and the Hamilton anxiety and depression test. A reliable nootropic effect of the drug was revealed, as well as its effect on cerebrosthenic and somatovegetative manifestations. There were no serious adverse events requiring additional measures.